PEMBERDAYAAN KELOMPOK TANI MELALUI PENGEMBANGAN UMKM DALAM MENINGKATKAN EKONOMI LOKAL DESA TONASA KECAMATAN SANROBONE TAKALAR - Agustuty, Lasty; Yazin, Nurfatwa Andriani; Artiyany, Megawhati; Kapriani, Kapriani (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2024)
This community service activity aims to empower farmer groups in Tonasa Village through the development of micro, small, and medium enterprises (MSMEs) as a strategy to enhance the local economy. The implementation method was carried out in stages, including observation, program planning, socialization, training, and continuous assistance. The results show an increase in farmers' skills in managing businesses, processing agricultural products into value-added goods, and understanding basic management and marketing principles.